Qualitative Study Of Complementary Breast Milk Food Provision By Toddler Mothers Among The Taa Tribe In South Batui District, Banggai Regency - Ramli Ramli; Muhammad Syafar; Veni Hadju; Aminuddin Syam; Sukri Palutturi; Yahya; Shanty Rizkiyani; Yustiyanti Monoarfa; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Providing Complementary Food for Breast Milk (MP-ASI) is an important stage in the nutritional intake of children after the age of 6 months. Socio-cultural influences play a significant role in the practice of providing MP-ASI, which includes traditions, diet, family values, and economic limitations. Children aged 0-24 months in fulfilling their nutritional intake in certain ethnic cultures also influence the provision of complementary food for breast milk (MP-ASI) to toddlers . This study aimsTo determine the pattern of providing complementary foods to breast milk in mothers of the Taa tribe in South Batui, Banggai Regency . Method: This study uses a qualitative approach, by conducting Focus Group Discussion (FGD), in-depth interviews, and observations of 10 mothers of Baduta Suku Taa as informants, as well as community leaders and cadre leaders as key informants selected by purposive sampling . Qualitative data processing is carried out by Theme analysis . Data analysis according to Miles and Huberman: data reduction, data presentation, and drawing conclusions. Data validity testing uses triangulation of methods and sources , and data is presented in Narrative form. Results: The pattern of providing complementary foods for breast milk (MP-ASI) in the Taa tribe has a tradition in the local term"Pusiri "is found among the Taa tribe in giving first food to childrenaccompanied by rituals and prayers that are repeated 7 times with the intention that the child will be healthy, strong and have abundant fortune for seven generations, and the type of food givenpreferred type of bananaIn the local language it is called Louwe banana which is boiled and mashed or filtered. The Pusiri tradition is carried out by parents in the family such as grandmothers or mothers. The provision of MP-ASI to Taa Tribe toddlers is generally given before the toddler reaches 6 months of age.namely at the age of 4, 5, and 6 months. The types of MPASI given also vary, namely homemade MPASI and manufactured MPASI . Processed MPASI is in the form of strained porridge, boiled bananas, and mashed tubers, while manufactured MPASI is in the form of SUN porridge. The frequency of giving MP - ASI varies , namely given 2 to 3 times a day. The mothers of the Taa Tribe Toddlers provide MP-ASI, most of which are not appropriate in terms of texture that is adjusted to the age of the Toddler, and the provision of MP-ASI is not yet diverse, especially in fulfilling vegetables and fruits. Conclusion: Pusiri tradition was found in the pattern of providing MPASI to Taa Tribe mothers which was carried out before the toddler was 6 months old. In general, the provision of MP-ASI to Taa Tribe toddler mothers is not appropriate in terms of the time of administration, MP-ASI texture, frequency and diversity . Routine assistance is needed for toddler mothers in providing the right MP-ASI.